1994
DOI: 10.1111/j.1432-1033.1994.tb18785.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenous lipid distribution among chlorophyll‐binding proteins of photosystem II in maize mesophyll chloroplasts

Abstract: Photosystem I1 membrane fractions from dark-adapted mesophyll chloroplasts of maize were solubilized in different concentrations of dodecyl P-D-maltoside. Chlorophyll-binding proteins from photosystem I1 were isolated either by ultracentrifugation on a sucrose gradient, or by flat bed isoelectric focusing and identified by gel electrophoresis analysis for their polypeptide composition. Lipid and fatty acid compositions were determined in complexes prepared by both methods and also in purified light-harvesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…Another explanation is that this complex so readily adopts the quenched state in vitro that xanthophylls are not limiting. This idea may relate to the greater hydrophobicity of the complex arising from the higher lipid-to-protein ratio (Tremolieres et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that this complex so readily adopts the quenched state in vitro that xanthophylls are not limiting. This idea may relate to the greater hydrophobicity of the complex arising from the higher lipid-to-protein ratio (Tremolieres et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Since these lipids are linked to specific structures of the photosystems, the lipid asymmetry of the thylakoids is likely to reflect the organisation of the photosynthetic machinery [24]. It has also been proposed that the asymmetry is preestablished in the inner envelope membrane due to the topography of lipid synthesising proteins and is transferred to thylakoids by membrane fusion [25].…”
Section: Energy-dependent Translocasesmentioning
confidence: 99%
“…Grana partitions are made up essentially of proteins with very little lipids, which are tightly bound to photosynthetic complexes (Tremolieres et al, 1994). Previous work on negatively stained PSII membranes and cryo-EM analysis of negatively and unstained membranes has shown that tetrameric PSII particles protrude from the membrane plane, while Lhc particles are located in the dark background (Simpson, 1979).…”
Section: The Topology Of Grana Membranes Is Affected By Mutationsmentioning
confidence: 99%
“…PSII organized into ordered arrays restricts protein dynamics and limits the PQ diffusion. While the surface occupancy of randomly organized PSII and LHCII particles is 0.72 to 0.77 (Tremmel et al, 2003), ordered C2S2 arrays leave very little space in between particles (Morosinotto et al, 2006), thus allowing PQ diffusion only in boundary lipids tightly bound to membrane complexes (Tremolieres et al, 1994). This is fully consistent with the analysis of fluorescence induction curves (Figure 8; see Supplemental Figure 5 online), where the last phase (J-P), reflecting the reduction of acceptors downstream of PSII, primarily PQ, is delayed by five times in koCP24 with respect to the wild type.…”
Section: How Does the Lack Of Cp24 Affect Growth And Etr?mentioning
confidence: 99%